ANALISIS PENGUJIAN BENDING KOMPOSIT SERAT SABUT KELAPA (COCOS NUCIFERA) DENGAN MATRIKS POLYESTER SEBAGAI BAHAN COVER INTAKE MANIFOLD - Rahmat; Faizin, Kholis Nur; Majedi, Farid (Pengelolaan Penerbitan Publikasi Ilmiah (P3I) Politeknik Negeri Madiun, 2024)
Composites are formed from a combination of fiber and matrix. Fiber functions as a reinforcing material that makes up the composite. The matrix functions to bind the fibers. Composites are useful as alternative materials such as iron, steel, metal and ceramic because they have advantages including biodegradability and corrosion resistance, making composites a potential new material to be developed. This research focuses on analyzing coconut fiber composites with a polyester resin matrix with varying fiber volume fractions of 30%, 35% and 40% using the hand lay-up method to determine the mechanical properties through the ASTM D790 Bending test. The highest average bending strength value is 65.32 N/mm^2, namely at a coconut fiber volume fraction of 40%. The best results from benchmark bending testing in making Intake Manifold Cover products to minimize the use of plastic materials in vehicle components.